Maternal age and congenital anomalies: 11 years of the national registry of congenital anomalies - Braz, Paula (2015)
Background: Congenital anomalies (CA) can be defined as structural or functional anomalies that occur during pregnancy and can be identified prenatally, at birth or later in life. In Portugal, since 1997 the Nacional Registry of Congenital Anomalies (RENAC), a population-based registry, is a strategic instrument in surveillance and improve knowledge in this field. The aim of this study is to investigate for the period 2000-2010, the relationship between maternal age, young or advanced and the risk of structural congenital anomalies.